Isinga: Objectification and Abjection in Women - Wafa, Abu; Akmal, Ramayda (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2024)
Isinga (2015) by Dorothea Rosa Herliany tells about the downturn of women so that they often become objects of the patriarchal system adopted by the local culture as well as the potential to cause abjection of female figures. This study attempts to analyze Isinga (2015) with Kristeva's perspective on abjection and Calogero's objectification of women. By using qualitative methods, this study used a feminist approach to see gender inequality in the novel. The results obtained from this study are that Irewa experienced objectification, which then continued to become an abjection. Irewa's objectification occurred because her husband, Malom, made her a sexual object. Jingi only received abjection since she was born because she was born with twins with Irewa, one of whom had to be thrown away so that the village would not be in danger.Isinga (2015) by Dorothea Rosa Herliany tells about the downturn of women so that they often become objects of the patriarchal system adopted by the local culture as well as the potential to cause abjection of female figures. This study attempts to analyze Isinga (2015) with Kristeva's perspective on abjection and Calogero's objectification of women. By using qualitative methods, this study used a feminist approach to see gender inequality in the novel. The results obtained from this study are that Irewa experienced objectification, which then continued to become an abjection. Irewa's objectification occurred because her husband, Malom, made her a sexual object. Jingi only received abjection since she was born because she was born with twins with Irewa, one of whom had to be thrown away so that the village would not be in danger.